2007
DOI: 10.1002/ajpa.20677
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of maternal lineage and biogeographic analyses of ancient and modern Hungarian populations

Abstract: The Hungarian language belongs to the Finno-Ugric branch of the Uralic family, but Hungarian speakers have been living in Central Europe for more than 1000 years, surrounded by speakers of unrelated Indo-European languages. In order to study the continuity in maternal lineage between ancient and modern Hungarian populations, polymorphisms in the HVSI and protein coding regions of mitochondrial DNA sequences of 27 ancient samples (10th-11th centuries), 101 modern Hungarian, and 76 modern Hungarian-speaking Sekl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
107
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(123 citation statements)
references
References 69 publications
12
107
0
3
Order By: Relevance
“…The decrease of N1a could, for example, be explained by the progressive disappearance of elite lineages through time. Such a phenomenon has recently been described in Hungary, where Tömöry et al (2007) demonstrated the rapid and comprehensive dilution of the haplogroups associated with the Magyar conquerors. Finally, large-scale movements of people in Europe are recorded in both the archaeological record and in historical accounts.…”
Section: Discussionmentioning
confidence: 94%
“…The decrease of N1a could, for example, be explained by the progressive disappearance of elite lineages through time. Such a phenomenon has recently been described in Hungary, where Tömöry et al (2007) demonstrated the rapid and comprehensive dilution of the haplogroups associated with the Magyar conquerors. Finally, large-scale movements of people in Europe are recorded in both the archaeological record and in historical accounts.…”
Section: Discussionmentioning
confidence: 94%
“…However, the current low frequency of those markers is not what one would expect to observe, had a substantial demographic replacement occurred (Nadasi et al, 2007; Hellenthal et al, 2014). Careful analyses of 10th century ancient DNA in Hungary showed a predominance of European mitochondrial haplotypes in burials attributed to the lower classes, and a high incidence of Asian haplotypes in high‐status individuals of that period (Tömöry et al, 2007), which points to the Asian immigrants as representing a social élite, rather than the bulk of the population. The exception to the results of the present study is thus nicely justified in this scenario, suggesting that when a Finno‐Ugric language was introduced in Hungary, the genetic buildup of the population changed only in part, thus retaining similarities with its geographic neighbors, an example of the process called élite dominance by Renfrew (1992).…”
Section: Discussionmentioning
confidence: 99%
“…The question of social stratification has been posed for Etruscan groups, and palaeogenetic results may support the hypothesis of elite class extinction during an assimilation process [63] . The progressive disappearance of elite lineages through time has also been described in Hungary, where the rapid and comprehensive dilution of the haplogroups associated with the Magyar conquerors has been demonstrated [60] . The same question can even be posed for more remote periods, such as the Neolithic.…”
Section: A Genetic Break With the Pastmentioning
confidence: 99%